2004
DOI: 10.1111/j.1365-246x.2004.02412.x
|View full text |Cite
|
Sign up to set email alerts
|

A new seismic tomography of Aigion area (Gulf of Corinth, Greece) from the 1991 data set

Abstract: S U M M A R YA new three-dimensional delay traveltime tomography is performed to image the intermediate structure of the western Gulf of Corinth. A large data set, collected in 1991 during a two-month passive tomographic experiment, has been reanalysed for the reconstruction of detailed Vp and Vs images. An improved tomography method, based on an accurate traveltime computation, is applied to invert simultaneously delayed P and S first-arrival traveltimes for both velocity and hypocentre parameters. We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
98
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 55 publications
10
98
1
4
Order By: Relevance
“…This data set has been used as well to perform tomographic studies. First results were obtained by LE MEUR et al (1997) and new velocity models were constructed by LATORRE et al (2004b) using an improved tomographic technique. LATORRE et al (2004b) found a two-layer vertical structure and the presence of a high Vp/Vs anomaly at depth, suggesting a possible role of fluids in the rifting process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This data set has been used as well to perform tomographic studies. First results were obtained by LE MEUR et al (1997) and new velocity models were constructed by LATORRE et al (2004b) using an improved tomographic technique. LATORRE et al (2004b) found a two-layer vertical structure and the presence of a high Vp/Vs anomaly at depth, suggesting a possible role of fluids in the rifting process.…”
Section: Introductionmentioning
confidence: 99%
“…First results were obtained by LE MEUR et al (1997) and new velocity models were constructed by LATORRE et al (2004b) using an improved tomographic technique. LATORRE et al (2004b) found a two-layer vertical structure and the presence of a high Vp/Vs anomaly at depth, suggesting a possible role of fluids in the rifting process. Despite important results, the quality of the 1991 data is limited because of many vertical single component (1C) stations, imposing a major limitation in constraining the mid-crust structure and the seismicity distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts to record the intense microseismicity in the study area were made in the past three decades. In 1991, a local network consisted of 51 seismological stations was installed in the western Corinth Gulf and operated for two months (Rigo et al 1996;Latorre et al 2004). During the summer of 1993, a temporary seismological network was installed over a period of seven weeks around the eastern Corinth Gulf (Hatzfeld et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The code developed by Monteiller (2005) has been already applied in several studies (Latorre et al 2004;Vanorio et al 2005;Gautier et al 2006;Theunissen et al 2012b). It is a linearized, iterative and damped least-square approach.…”
Section: Local Tomographymentioning
confidence: 99%